2021
DOI: 10.1177/23259671211009263
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescribing Habits for Common Arthroscopic Procedures in Opioid Naïve Patients

Abstract: Background: With the opioid epidemic and the increasing number of opioid-related deaths, there is growing awareness in the medical community regarding the dangers of opioid overprescription. As a result, there is a willingness among physicians to abandon old norms and adopt new data-driven prescribing practices. Purpose: To demonstrate patient-reported consumption data of opioid medications after anterior cruciate ligament (ACL) reconstructions (ACLRs), knee arthroscopies, and rotator cuff repairs to provide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In a recent study, Thompson et al. 14 reported an increasing opioid use with age, the lowest use being in the <17 years of age category. Sayegh et al.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a recent study, Thompson et al. 14 reported an increasing opioid use with age, the lowest use being in the <17 years of age category. Sayegh et al.…”
Section: Discussionmentioning
confidence: 95%
“…Thompson et al. 14 reported that the mean number of pills taken following ACLR was 19 ± 15 in their cohort and suggested that prescribing 20 pills of 5-mg hydrocodone/325-mg acetaminophen would provide satisfactory pain management after ACLR. Similarly, Sayegh et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…contrast with our initial hypothesis that male patients and those of a younger age group would take more opioids and report lower satisfaction scores compared with female patients and an older demographic group. The assertion that opioids are prescribed in excess following ACLR and other arthroscopic procedures is not novel, as some reports have suggested that 25% to 88% of patients are prescribed more pills than are required postoperatively [15][16][17] . In the present study, >40% of all opioids prescribed for patients after ACLR went unused, again supporting previous literature and underscoring an opportunity for the orthopaedic surgeon to refine opioid prescription practices to achieve the acceptable minimum or even avoid opioids altogether.…”
Section: Table II Mme Consumptionmentioning
confidence: 99%